MMS: Technologies, Usage and Business Models - Ralph, Daniel (John Wiley & Sons, 2011)
MMS has evolved from the huge popularity of the SMS text service for GSM networks. It is a departure from the transport mechanism used for SMS (which is based on the GSM signalling channels) to the use of IP to transport messages within the MMS network. To this end MMS has similarities with Internet email and standard IETF protocols. As with any new technology it is difficult to accurately predict the position within the next 5 years, although based on previous experience with WAP and SMS it would be fair to say that these protocols will increase in usage over the next 5 years and become legacy for a further 5 years following which, users will migrate onto the next wave of messaging. Significant revenue growth and data usage is expected to be driven by consumer usage of MMS.